Migration in Russia. What Causes Antimigrant Sentiment? - Savelyeva, Alla (My University, 2013)
Post-Soviet territory represents one of the biggest migration hubs in the world.Russian labor intensive economy and vast labor market have been attracting millions of migrants from more than a hundred countries.However, the majority of migrants come from former Soviet republics.For the past 10 years city dwellers have developed a strong dislike to migrants. Migrants are blamed for all social ills in Russia.This study looks at causes of antimigrant sentiment in contemporary Russia.It relies on secondary data analysis as well as analysis on policies of Russian Federal Migration Service.My claim is that antimigrant sentiment in Russia is the result of socio-economic and political transformations in society and lack of opportunities as well as widespread corruption in state institutions.Hostility to migrants is also invoked by the scale of migration-currently Russia is hosting up to ten million migrants.Moreover,current migration policy increases the number of illegal migrants due to bureaucracy and ineffectiveness.
Keywords: Public and International Affairs; Russia Federation -- Social conditions; Migration, Internal -- Russia Federation; Russia Federation -- Emigration and immigration